DEVELOPMENT OF REGIONAL TSS ALGORITHM OVER PENANG USING MODIS TERRA (250 M) SURFACE REFLECTANCE PRODUCT - Mat Amin, Abd Rahman; Abdullah, Khiruddin; Hwee , San Lim; Embong, Muhd Fauzi; Ahmad, Fadhli; Yaacob, Rosnan (De Gruyter Open, 2016)
Total suspended sediment (TSS) plays a significant role in the environment. Many researchers show that TSS has a high correlation with the red portion of the visible light spectrum. The correlation is highly dependent on geography of the study area. The aim of this study was to develop specific algorithms utilizing corrected MODIS Terra 250-m surface reflectance (Rrs) product (MOD09) to map TSS over the Penang coastal area. Field measurements of TSS were performed during two cruise trips that were conducted on 8 December 2008 and 29 January 2010 over the Penang coastal area. The relationship between TSS and the surface reflectance of MOD09 was analysed using regression analysis. The developed algorithm showed that Rrs are highly correlated with the in-situ TSS with R2 is 0.838. The result shows that the Rrs product could be used to estimate TSS over the Penang area.